Communication: Isotopic effects on tunneling motions in the water trimer - Videla, Pablo Ernesto (2016)
We present results of ring polymer molecular dynamics simulations that shed light on the effects of nuclear quantum fluctuations on tunneling motions in cyclic [H2O]3 and [D2O]3, at the representative temperature of T = 75 K. In particular, we focus attention on free energies associated with two key isomerization processes: The first one corresponds to flipping transitions of dangling OH bonds, between up and down positions with respect to the O-O-O plane of the cluster; the second involves the interchange between connecting and dangling hydrogen bond character of the H-atoms in a tagged water molecule. Zero point energy and tunneling effects lead to sensible reductions of the free energy barriers. Due to the lighter nature of the H nuclei, these modifications are more marked in [H2O]3 than in [D2O]3. Estimates of the characteristic time scales describing the flipping transitions are consistent with those predicted based on standard transition-state-approximation arguments.